2012
DOI: 10.2478/v10086-012-0009-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of feeding juvenile tench (Tinca tinca (L.)) feeds supplemented with vegetable oils on hematological indexes and liver histology

Abstract: Citation: Demska-Zakêoe K., Zakêoe Z., Ziomek E., Jarmo³owicz S. 2012 -Impact of feeding juvenile tench (Tinca tinca (L.)) feeds supplemented with vegetable oils on hematological indexes and liver histology -Arch. Abstract. The aim of the study was to identify the impact of feeding juvenile tench commercial feed supplemented with fish oil, linseed oil, arachide oil, and rapeseed oil on the hematology, cytology, and histology indexes of the liver. The fish were reared in a recirculating system and fed feed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…According to Babalola et al (2009), erythrocyte count in Heterobranchus longifilis was significantly affected by a dietary lipid source (higher in fish fed with sunflower and poultry lipids compared to those fed with other vegetable or animal fat). A significant effect of the lipid source on erythrocyte count was confirmed by Demska-Zakęś et al (2012) for Tinca tinca. Rigos et al (2010) reported an increase in RBC of S. aurata fed with food supplemented with iron.…”
Section: Erythrocytessupporting
confidence: 52%
“…According to Babalola et al (2009), erythrocyte count in Heterobranchus longifilis was significantly affected by a dietary lipid source (higher in fish fed with sunflower and poultry lipids compared to those fed with other vegetable or animal fat). A significant effect of the lipid source on erythrocyte count was confirmed by Demska-Zakęś et al (2012) for Tinca tinca. Rigos et al (2010) reported an increase in RBC of S. aurata fed with food supplemented with iron.…”
Section: Erythrocytessupporting
confidence: 52%
“…It is likely that a histological assessment of the liver with such altered external structure would reveal pathological changes (e.g. hepatocyte congestion, hepatocyte lipid vacuolization) that were described in experiments in which tenches received feed containing 50 g/kg arachide or linseed oil (Demska‐Zakęś, Zakęś, Ziomek & Jarmołowicz, ). Interesting are also the results of histological analyses in the tilapia published by Aydin, Gümüş & Balci ().…”
Section: Discussionmentioning
confidence: 99%
“…2). Demska-Zakes et al (2012) reported congestion, vacuolisation in hepatocytes, nuclear chromatin and nucleus disintegration when supplementary feed containing vegetable oil was offered to juvenile tench (Tinca tinca). Vacuolation in hepatocytes with pyknotic nuclei were observed in fish fed on FM diet Effect of different feed ingredients on digestive enzymes activity in Labeo rohita (Fig.…”
Section: Resultsmentioning
confidence: 99%